Garding's Inequality for Elliptic Differential Operator with Infinite Number of Variables - Ahmed Zabel; Maryam Alghamdi (International Journal of Mathematics and Mathematical Sciences)
We formulate the elliptic differential operator with infinite number of variables and investigate that it is well defined on infinite tensor product of spaces of square integrable functions. Under suitable conditions, we prove Garding's inequality for this operator.